Commoning the commons: A sourcebook to strengthen management and governance of water as commons - Foundation for Ecological Security; International Crops Research Institute for the Semi-Arid Tropics; International Food Policy Research Institute (Foundation for Ecological Security, 2021)
Water is essential for the survival and sustenance of ecosystems and human societies. We are also aware that water is finite and a limited resource that is getting scarcer. People across the globe are experiencing a water crisis and this crisis is largely our own making. Globally, over 2 billion people live in countries experiencing high water stress (UN, 2018). In India, 54 percent of the country faces high to extremely high water stress (WRI, 2014) and India ranks 13th among the world’s ‘extremely water-stressed countries (WRI, 2019). The existing climate change scenario further amplifies the crisis and its impact on people.